Human Capital and Regional Economic Growth in Indonesia: A Spatial Analysis Approach - Windhani, Kikin; Purwaningsih, Yunastiti; Mulyaningsih, Tri; Samudro, Bhimo Rizky; Hardoyono, Fajar (Faculty of Geography, Universitas Gadjah Mada, 2023)
Endogenous growth theory assumes that human capital is a prominent factor in regional economic growth. However, the imbalance of human capital between regions is still a major problem in economic growth in Indonesia. Previous studies on regional economic growth have recognized the importance of considering spatial aspects as a determinant of regional economic growth. The geographical area in the form of an archipelago with a large number of administrative districts and cities produces pros and cons regarding the influence of spatial aspects on the regional growth of urban districts. This study aims to analyze the distribution of human capital using the Alternative Human Development Index (AHDI) approach and the effect of human capital and spatial aspects on the regional economic growth of urban districts in Indonesia within the framework of endogenous growth theory. The research method uses geometric mean to measure the Alternative Human Development Index, Geographic Information System (GIS) to see the distribution of human capital and regional economic growth in Indonesia, and the spatial regression Spatial Autoregressive Moving Average (SARMA) used to analyze the spatial aspects of human capital and regional economic growth in Indonesia. The results show that human capital in Indonesia is still unequal between the western and eastern parts of Indonesia. Human capital and spatial factors have positive effects and are the most influential determinants of Indonesia's regional economic growth, as indicated by the value of the spatial lag weight matrix of the dependent variable (ρ) and the spatial error term (λ) that is positive.